Teachers’ Talk and Its Impact on Young Learners’ Interaction in The Learning Environment - Cahyani, Dian Anik; Chotimah, Ima Chusnul (SALEE: Study of Applied Linguistics and English Education, 2023)
Teacher talk otherwise opportunities for second language learning. However, teachers are often unaware how their talk in?uences opportunities for students’ language development in the classroom. This study explores teachers’ talk and its impact on young learners’ interaction in learning environment specifically in Raudhatul Athfal (RA) Muslimat Arif Rahman Jombang. This research using a qualitative design and the data collection techniques from recorded audio-visually; teachers’ talk transcripts; events or occasions which directly or indirectly influence the teachers’ talk. The researchers employ several instruments such as documentation, observation and interview. Data reduction, data presentation, and drawing conclusions were used in the data analysis technique. The finding of this research from the indirect influence category, namely: (1) deals with feelings, (2) Praises or encourages, (3) Uses students’ ideas, and (4) Asks questions. While in the direct influence category, there are five sub categories namely: (1) Gives Information, (2) Corrects without rejections, (3) Gives directions, (4) Criticizes students’ behavior, and (5) Translating (code-switching). It encourages the teacher to look up-close at their teachers’ talk in order to raise their awareness of its impact on language learning.